Assessment of Energy Performance on Turning Process based on Motor Power Capacity of Lathe Machine - HALOMOAN SINAGA - (13113010), RUDY
This year, the number of industries in Indonesia continues to increase, especially in the manufacturing industry, and the manufacturing industry dominant uses electrical energy as the main energy for its propulsion machinery. On the other hand, electrical energy is generated from the burning process of fossil fuels that can produce pollution that has a negative impact on the environment, such as the effects of global warming and acid rain. So it takes a concept to reduce the negative impact of the concept of "green manufacturing". Lathes are one of the most widely used machines in machining processes in various industries. This lathe will be analyzed the performance of electric energy use in a turning process, so it can be determined how well the performance of energy use of the lathe. Specific energy consumption (SEC) indicator is used in determining energy level on a machine based on certain material removal rate (MRR) level. The data envelopment analysis (DEA) method is used to obtain the most efficient energy usage performance. This method works by comparing the SEC of several machines over a certain MRR range with similar engine capacity and determining the minimum SEC on each particular MRR. This minimum SEC will be the reference value, and if the reference value is linked it will become a reference curve. Then the performance assessment is done by assessing how far the engine curve is viewed with the reference curve, if closer to the reference curve the better the machine's energy usage. Otherwis,e if the engine curve is reviewed further with the reference curve it can be said the worse the performance of its energy use. This reference curve can be used as a reference for the assessment of the performance of other machines in any location for the same power capacity of the driving force. If using this data for 1-2 kW engine capacity Krisbow 3 engine from SMK Negeri 2 is best, while for capacity> 2-4 kW Horison M300 engine performance from Bandung workshop is the best. Axelson machine from Bandung workshop on capacity> 6 kW has the worst energy use performance in its category.